Adaptive resource allocation to stochastic multimodal projects: a distributed platform implementation in Java - Tereso, Anabela Pereira (2006)
This paper presents the implementation of the dynamic programming model (introduced in a previous paper) for the resolution of the adaptive resource allocation problem in stochastic multimodal project networks. A distributed platform using an Object Oriented language, Java, is used in order to take advantage of the available computational resources.